To use the Zero-Product Property, just follow these simple steps:
Factor the Equation: Start with an equation like (x^2 - 5x + 6 = 0). You need to break it down into parts. Here, it factors to ((x - 2)(x - 3) = 0).
Set Each Part to Zero: The cool thing about this property is that if a multiplication gives us zero, then at least one part has to be zero. So, we set (x - 2 = 0) and (x - 3 = 0).
Solve for (x): Now we find the answers! From (x - 2 = 0), we get (x = 2). And from (x - 3 = 0), we find (x = 3).
Don't forget, practicing with different equations will really help you get the hang of it!
To use the Zero-Product Property, just follow these simple steps:
Factor the Equation: Start with an equation like (x^2 - 5x + 6 = 0). You need to break it down into parts. Here, it factors to ((x - 2)(x - 3) = 0).
Set Each Part to Zero: The cool thing about this property is that if a multiplication gives us zero, then at least one part has to be zero. So, we set (x - 2 = 0) and (x - 3 = 0).
Solve for (x): Now we find the answers! From (x - 2 = 0), we get (x = 2). And from (x - 3 = 0), we find (x = 3).
Don't forget, practicing with different equations will really help you get the hang of it!